KELAYAKAN MEDIA POP-UP BOOK SUB MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN KELAS VIII IPA MTSN 2 PONTIANAK - Daningsih, Entin; Ismail, Ismail; Titin, Titin (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: The learning process of sub-material of structure and function of plant tissue was conducted by discussion with the aid of two-dimensional media in small sizes. Laboratory work activities cannot be carried out in school while students are required to understand various tissues in plant organs. Thus, a media is needed that can attract students' attention, motivation and make it easier for students to distinguish plant tissue. This study aimed to develop pop-up book media equipped with pictures and learning materials. Methods: Research and Development (R&D) was used to develop pop-up book media. The development steps were (1) potential and problems, (2) data collection, (3) product design, and (4) validation. The techniques used in media development were pull-tabs, transformation, and tunnel books. The instrument used was questionnaire with a Likert scale rating. Data analysis used the calculation of Content Validity Index (CVI) using the Lawshe’s method. Results: Pop-up book media on the structure and function of plant tissue sub-materials were developed using pull-tabs, transformation, and tunnel books techniques based on four stages in R&D. The results of the CVI calculation obtained 0.99. Conclusion: The pop-up book media which was developed using the techniques of pull-tabs, transformation, and tunnel books obtained a CVI of 0.99 with five validators. Based on this CVI, the media was feasible to use for learning process.